Do valor da vida humana e da vida humana sem valor - Rocha, Francisco Ilídio Ferreira (2014)
This thesis has the purpose of analyzing the current state of the constitutional protection of human life and, from this, specifies the axiological dimension of the vital existence of the human being. In this sense, it pursues the goal to establish, legally, what is life as a constitutional and legal interest worthy of protection, stating its definition and separating it by differentiation of those so called life related rights. These conceptual foundations are indispensable to the attainment of what is intended as a legal-axiological study of human life, which allows to recognize that, despite the imperatives derived from the principle of human dignity, the legal protection of human life realizes in different degrees of intensity and from arbitrary criteria in a way that allows the deduction that human life is considered more or less valuable in certain circumstances and, in some cases, one can even say that the biological life of the human being does not have any value at all. Identification of thecritical circumstances implying varying degrees of protection of life, as well as those authorizing the abandonment and denial of its value, constitutes the core of this thesis